Synthesis and characterization of ZrO2@SiO2 core-shell nanostructure as nanocatalyst: Application for environmental remediation of rhodamine B dye aqueous solution - Padovini, D. S.S. [UNESP]; Magdalena, A. G. [UNESP]; Capeli, R. G. [UNESP]; Longo, E.; Dalmaschio, C. J.; Chiquito, A. J.; Pontes, F. M. [UNESP] (Elsevier, 2019)
ZrO2@SiO2 core-shell nanostructures were synthesized by a facile two-step hydrothermal plus Stöber chemical route. The structure, morphology and properties of the nanoparticles were characterized using X-ray powder diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), UV–Vis spectroscopy, zeta-potential measurements, transmission electron microscopy (TEM) and high-resolution transmission electron microscopy (HRTEM). XRD confirmed the presence of tetragonal ZrO2 crystalline and amorphous SiO2 phases. FTIR analysis confirmed the existence of Zr-O-Si bonds at the surface of the core-shell nanostructures. According to the UV–Vis spectroscopy measurements, the energy band gap value of the uncoated ZrO2 nanoparticles was estimated to be 5.13 eV and the excitation energy (energy band discontinuity) of the ZrO2@SiO2 core-shell nanostructures was found to be 2.31 eV. Transmission electronic microscopy results showed 5–8 nm ZrO2 nanoparticles highly crystalline and fully covered by amorphous and uniform SiO2 layer 10–15 nm wide, which is an evidence of the core-shell structure. Photocatalytic performance of ZrO2@SiO2 core-shell nanostructures was carried out using rhodamine B dye in aqueous solution at room temperature under UV light irradiation. ZrO2@SiO2 core-shell nanostructures showed better photocatalytic activities in comparison to the as prepared ZrO2 and SiO2 samples. The enhanced photocatalytic performance for ZrO2@SiO2 core-shell nanostructures may be the result of the Zr-O-Si interfacial layer narrowing the energy gap needed to electron-hole pairs creation, thus enhancing photoinduced charges generation and reducing charges recombination.
Keywords: Hydrothermal; Photocatalysis; Rhodamine B; ZrO2@SiO2 nanostructure